A metodologia do Aprendizagem Sequencial nas percepções e ações de participantes de atividades formativas em Educação Ambiental - Maragni, Arianne Rabelo Brianezi (2014)
This dissertation discusses the training workshop “Vivências com a Natureza” (offered by the Associação Brasileira de Vivências com a Natureza, Instituto Romã) from May 2003 until June 2012. The survey consists on mapping the educators who have participated, their professional actions using the methodology, what impact on their personal and professional lives it has had and how the methodology relates to Environmental Education. It also examines the complementarity between the processes of awareness and knowledge within the field of the Environmental Education. The results indicate that educators work with the Flow Learning methodology because they believe that consciousness-raising processes are important to start changing behavior and attitudes in the environmental area. They also believe that information and more objective questions are complementary to this process.